Oltiin kerran vähän kahdestaan ; Kulta polkee fillarillain - Tervomaa, Jonna, 1973-; VIP-Music ([Kustannuspaikka tuntematon] : VIP-Music, 1984)
2 kappaletta
Jonna (lauluääni).
Keywords: Tervomaa, Jonna, -- 1973- -- singlet